2023
DOI: 10.1097/md.0000000000032507
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional printing designed customized plate in the treatment of coronal fracture of distal humerus in teenager: A case report

Abstract: Rationale: Because of the complicated anatomy and considerable change in size and morphology with age in teenagers, the appropriate internal fixator of coronal shear fracture of distal humerus is difficult to choose, and therefore, the fixation of this kind of fracture is difficult and controversial. Furthermore, distal humeral fractures in teenagers often involve the epiphysis, the rigid fixation of fracture and the simultaneous minimally invasive and protection of the epiphysis are contradictory. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…We carried out a narrative review of the pediatric literature for capitellar shear fractures (shown in Table 1 ). Most of the literature consists of case reports ( 5 8 , 13 , 16 , 17 , 20 23 , 25 27 , 29 31 , 33 , 38 ), followed by a smaller number of retrospective case series ( 9 , 18 , 19 , 24 , 28 , 32 , 34 37 ). The retrieved literature showed a bimodal distribution of these fractures, with a first peak in childhood (<10 years) ( 7 , 17 , 20 , 31 ) and a second one, the most representative, in pre-adolescents and adolescents ( 5 9 , 13 , 16 , 18 , 19 , 21 25 , 27 30 , 32 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We carried out a narrative review of the pediatric literature for capitellar shear fractures (shown in Table 1 ). Most of the literature consists of case reports ( 5 8 , 13 , 16 , 17 , 20 23 , 25 27 , 29 31 , 33 , 38 ), followed by a smaller number of retrospective case series ( 9 , 18 , 19 , 24 , 28 , 32 , 34 37 ). The retrieved literature showed a bimodal distribution of these fractures, with a first peak in childhood (<10 years) ( 7 , 17 , 20 , 31 ) and a second one, the most representative, in pre-adolescents and adolescents ( 5 9 , 13 , 16 , 18 , 19 , 21 25 , 27 30 , 32 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the literature consists of case reports ( 5 8 , 13 , 16 , 17 , 20 23 , 25 27 , 29 31 , 33 , 38 ), followed by a smaller number of retrospective case series ( 9 , 18 , 19 , 24 , 28 , 32 , 34 37 ). The retrieved literature showed a bimodal distribution of these fractures, with a first peak in childhood (<10 years) ( 7 , 17 , 20 , 31 ) and a second one, the most representative, in pre-adolescents and adolescents ( 5 9 , 13 , 16 , 18 , 19 , 21 25 , 27 30 , 32 38 ). The most frequent associated injury was the ipsilateral elbow dislocation, followed by the involvement of the medial or lateral condyle, or an olecranon or radial head fracture ( 5 , 16 , 17 , 21 , 31 , 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%